กลยุทธ์การบริหารโรงเรียนในพื้นที่สูงและทุรกันดาร : School Management Strategies of Remote Highland Areas - Chongkol Kaewko จงกล แก้วโก (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2021)
การวิจัยครั้งนี้มีวัตถุประสงค์ 1) เพื่อศึกษาสภาพแวดล้อม ความต้องการและแนวทางการบริหารโรงเรียนบนพื้นที่สูงและทุรกันดาร 2) เพื่อสร้างกลยุทธ์การบริหารโรงเรียนบนพื้นที่สูงและทุรกันดาร 3) เพื่อประเมินกลยุทธ์การบริหารโรงเรียนบนพื้นที่สูงและทุรกันดาร ขั้นตอนการวิจัยแบ่งเป็น 3 ขั้นตอน ขั้นตอนที่ 1 การศึกษาสภาพแวดล้อม ความต้องการการบริหารโรงเรียนบนพื้นที่สูงและทุรกันดาร กลุ่มตัวอย่างได้แก่ ผู้บริหารสถานศึกษาและครูผู้สอน จำนวน 383 คน เครื่องมือที่ใช้เป็นแบบสอบถาม การศึกษาแนวทางการบริหารโรงเรียนบนพื้นที่สูงและทุรกันดาร กลุ่มผู้ให้ข้อมูลได้แก่ผู้ทรงคุณวุฒิ จำนวน 12 คน เครื่องมือที่ใช้เป็นแบบสัมภาษณ์ การศึกษาแนวปฏิบัติที่ดีการบริหารโรงเรียนบนพื้นที่สูงและทุรกันดาร กลุ่มผู้ให้ข้อมูลได้แก่ผู้บริหาร ครูผู้สอนและกรรมการสถานศึกษา จำนวน 3 โรงเรียน เครื่องมือที่ใช้เป็นแบบสัมภาษณ์ ขั้นตอนที่ 2 การยกร่างและตรวจสอบร่างกลยุทธ์โดยผู้ทรงคุณวุฒิ จำนวน 9 คน ด้วยการสนทนากลุ่ม ขั้นตอนที่ 3 การประเมินความเป็นไปได้และความเป็นประโยชน์ กลุ่มตัวอย่างได้แก่ผู้บริหารโรงเรียน จำนวน 77 คน เครื่องมือที่ใช้เป็นแบบสอบถาม สถิติที่ใช้ในการวิเคราะห์ข้อมูลได้แก่ร้อยละ ค่าเฉลี่ยและส่วนเบี่ยงเบนมาตรฐาน และการวิเคราะห์เนื้อหา ผลการวิจัย พบว่า 1. สภาพแวดล้อมการบริหารโรงเรียนบนพื้นที่สูงและทุรกันดารมีจุดแข็งคือจัดโครงสร้างการบริหารงานโรงเรียนที่ชัดเจน จุดอ่อนคือครูมีภาระงานมาก โอกาสคือหน่วยงานภายนอกส่งเสริมและสนับสนุนการจัดการศึกษา อุปสรรคคือนักเรียนส่วนใหญ่เป็นกลุ่มชาติพันธ์ ความต้องการการบริหารโรงเรียนบนพื้นที่สูงและทุรกันดารพบว่าด้านบุคลากรมีความต้องการมากที่สุด และแนวทางการบริหารโรงเรียนบนพื้นที่ภูเขาสูงและทุรกันดาร พบว่าควรปรับโครงสร้างหลักสูตรให้สอดคล้องกับบริบทของสถานศึกษา 2. กลยุทธ์การบริหารโรงเรียนบนพื้นที่สูงและทุรกันดาร มีทั้งหมด 4 กลยุทธ์หลัก 16 กลยุทธ์ย่อย 62 มาตรการและ 48 ตัวชี้วัด 3. ผลการประเมินกลยุทธ์มีความเป็นไปได้อยู่ในระดับมาก และความเป็นประโยชน์อยู่ในระดับมากที่สุด The purposes of this research were 1) to study the environment, need, and guidelines for school management of remote highland areas. 2) to establish a strategies for the school management of remote highland areas. 3) The evaluation of the school mqnagement strategies of remote highland areas. The research consists of 3 step. For step 1, study the environment, need, and guidelines for school management of remote highland areas. The samples used in the research were 383 school administrators and teachers, 12 experts and school administrators, teachers and board of educational institutions, totaling 3 schools. The research instruments were interviews. The statistics used consisted of percentage, mean, and standard deviation and content analysis. For step 2, establish a strategies for the school management of remote highland areas. The focus group discussion was organized among 9 experts to confirm the propriety standard of the strategies. For step 3, evaluate strategies for the school management strategies of remote highland areas. The sample of this research consisted of 77 school administrators. The research instruments were questionnaires. Statistics employed for data analyses were mean and standard deviation. The results revealed that; 1. The environment of the school management of remote highlands areas found that the strength was the precise structure of school management. The weakness is that teachers had heavy workloads, both teaching and supporting affairs.Opportunities were external organizations to promote and support educational management. The obstacles were that most students were ethnic groups with different beliefs and values. The need of school management of remote highlands areas found that that the aspect with the highest need was personnel. And guidelines of school management of remote highlands areas found that adjust the curriculum structures to be in line with the context of educational institutions 2. The school management strategies of remote highland areas consists of 4 strategies, 16 sub-strategies, 62 measures and 48 indicators 3. The evaluation of the feasibility of strategies which was at a high level, and utility of strategies which was the most level.